FRI0303 Efficacy and safety of ustekinumab in patients with active systemic lupus erythematosus: results of a phase 2, randomised placebo-controlled study. (12th June 2018) - van Vollenhoven, R.; Hahn, B.H.; Tsokos, G.C.; Wagner, C.; Lipsky, P.; Hsu, B.; Chevrier, M.; Gordon, R.; Triebel, M.; Rose, S.
Abstract : Background: IL12 and IL23 have been linked to SLE pathogenesis. Objectives: The anti-IL12/23 monoclonal antibody ustekinumab (UST) was evaluated in pts with active SLE. Methods: We conducted a Ph2, PBO-controlled study in 102 pts with active SLE. Pts were randomised(3:2) to UST IV 6 mg/kg or PBO at wk0, followed by UST SC 90 mg or PBO injections q8w, both added to standard care. Primary endpoint was proportion of pts achieving SLE responder index(SRI)−4 response at wk24. Secondary endpoints were change from baseline(BL) in SLEDAI-2K, PGA and BICLA response. Additional pre-specified endpoint analyses included no BILAG worsening(defined as no new BILAG A and ≤1 new BILAG B) and BILAG flare(≥1 new BILAG A or ≥2 new BILAG B). Results: SRI-4 response occurred in 60% UST vs 31% PBO pts(p=0.005) at wk24 (table 1). UST pts had greater median change from BL in SLEDAI-2K and PGA vs PBO. No difference was observed in BICLA response at wk24; however, in the UST group vs PBO, more pts had no BILAG worsening, and the risk of a new BILAG flare was significantly lower(HR 0.11 [95% CI 0.01–0.94];p=0.0078). UST demonstrated improvement in musculoskeletal and mucocutaneous disease features vs PBO (table 1). Through wk24, 78% UST vs 67% PBO pts had ≥1 AE; 8.3%–9.5%, respectively, had ≥1 SAE; there were no deaths. The overall safety profile was comparable between UST and PBO. Conclusions: UST treatment showed efficacy in pts with active SLE and was well-tolerated. UST may work via a novel mechanism of action in SLE. Disclosure of Interest: R. van Vollenhoven Grant/research support from: Janssen Research and Development, LLC, B. Hahn Grant/research support from: Janssen Research and Development, LLC, G. Tsokos Grant/research support from: Janssen Research and Development, LLC, C. Wagner Employee of: Janssen Research and Development, LLC, P. Lipsky Grant/research support from: Janssen Research and Development, LLC, B. Hsu Employee of: Janssen Research and Development, LLC, M. Chevrier Employee of: Janssen Research and Development, LLC, R. Gordon Employee of: Janssen Research and Development, LLC, M. Triebel Employee of: Janssen Biologics, S. Rose Employee of: Janssen Research and Development, LLC